There's Plenty of Room at the Bottom: Low Radiation as a Biological Extreme - Wadsworth, Jennifer; Cockell, Charles S.; Murphy, Alexander StJ; Nilima, Athoy; Paling, Sean; Meehan, Emma; Toth, Christopher; Scovell, Paul; Cascorbi, Leander (Frontiers in Astronomy and Space Sciences, 2020)
The effects of high radiation as a biological extreme have historically been, and continue to be, extensively researched in the fields of radiation biology and astrobiology. However, the absence of radiation as an extreme has received relatively limited attention from the scientific community, with its effects on life remaining unclear. The currently accepted model of the radiation dose-damage relationship for organisms is the linear no-threshold (LNT) model, which predicts a positive linear correlation between dose and damage that intercepts at zero dose corresponding to zero damage. Despite its wide-spread implementation, the LNT model is continuously being challenged by various new models, with the hormesis model as one of its main competitors. This model also postulates damage at high doses but, in contrast to the LNT model, it predicts beneficial stimulation of growth at low doses. Experiments to date have not yet been able to conclusively validate or dismiss either of these models. The aim of the collaborative Subsurface Experiment of Life in Low Radiation (SELLR) project was to test these competing models on prokaryotes in a well-characterised environment and provide a robust experimental set up to investigate low radiation in terrestrial and non-terrestrial environments. Bacterial growth assays using Bacillus subtilis and Escherichia coli were performed under ultra low ionising radiation in the Boulby International Subsurface Astrobiology Laboratory (BISAL) facilities of the Boulby mine (Cleveland, UK) and were used to investigate effects on viability. No significant effect on bacterial growth was observed from exposure to radiation doses ranging from 0.01 times the levels of background radiation typically found in terrestrial surface environments to 100 times that background. These data suggest that the extremes of low radiation do not alter growth parameters of these two organisms and that an improved model should be considered for prokaryotes, consisting of a dose-damage response with a threshold at ultra low radiation. We discuss the implications of these data for low radiation as a novel microbiological “extreme”.